Connectivity and permeability of Zhuhai tight sandstone heterogeneous reservoirs from western Pearl River Mouth Basin (China) by nuclear magnetic resonance. (August 2022) - Zhou, Sandong; Deng, Yong; Wang, Hua; Pan, Zhejun; Yan, Detian
Abstract: Resolving pore attributes and connectivity of oil-bearing sandstone formations is key to the precise estimation of the oil storage and flowing capacity of the reservoirs. However, very few studies have quantitatively characterized the individual porosities of interconnected pores and inaccessible pores. This study addresses these research gaps by studying Zhuhai sandstone from the western Pearl River Mouth Basin, China, with very low to medium permeability (0.055–346 mD). Nuclear magnetic resonance (NMR) centrifugation distinguished the interconnected and inaccessible pores. NMR T 2 parameters ( T 2 cutoff and T 2g ) had a distinct impact on the connectivity index and irreducible water saturation. This study successfully developed an adaptable model that can efficiently estimate permeability in heterogeneous porous media, where no samples are taken, using NMR log. The permeabilities calculated by Schlumberger Doll Research, Coates-cutoff, Coates-BVI, and SDR-reg models were compared with those measured using a gas permeameter. Permeabilities were best calculated using flow-accessible porosity (i.e., Coates-BVI model, 95% matching) rather than other models. The connectivity (0.13–0.84) and movable fluid porosity (1.46–19.32%) were the primary factors that control permeability, and the fracture/crack attributes determined dual porosity. The study revealed that illite in clay minerals exerts a positive control on permeability by sheltering the interconnected primary porosity. Highlights: Moveable water spaces in sandstones are probed via low-field NMR. The influence of pore connectivity on gas transport capacity is established. A new Coates-cutoff-based method accurately estimates permeability using NMR logging.